Appointing high-court judges by political parties - Nicolás Porteiro; Antonio Villar (SERIEs - Journal of the Spanish Economic Association, 2015)
This paper proposes a mechanism to overcome the possibility that political parties may block the nomination of High-Court judges when the Parliament is involved in their nomination and theirmandate expires on a fixed date. This possibility arises when the default option is that the judge whose mandate expires holds office until an agreement is reached. Our proposal consists of changing the default option by a weighted lottery, related to the shares in Parliament of the different parties.We show that this mechanism is capable of solving the problem under reasonable conditions and implementing a politically balanced solution.
Keywords: D72; 330; Negotiation; Political competition; Random protocols; Legislative bargaining